Hubungan Senyawa Metabolit Pada Tanaman Meliaceae Terhadap Tingkat Serangan Hypsipyla robusta - Jefri Sembiring (Jurnal Biologi Papua, 2021)
This study aims to determine the relationship of metabolite compounds in meliaceae plants to the preference of Hypsipyla sp. This research was conducted at the Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Sam Ratulangi State University, Manado BALITKA Laboratory, Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, State University of Gorontalo and sending samples to the Pharmacy Laboratory of Sendai Japan to see the NMR structure. This study was designed in a Latin square design with 5 treatments and 5 replications. The total number of plants in all treatments was 250 plants. The determination of secondary metabolites was carried out in five stages, namely: 1) sample collection and processing, 2) extraction, 3) purification, 4) phytochemical test, 5) identification of compounds using UV-Vis and IR spectrophotometers. The sample materials used were dry samples of langsat, duku, mindi, and mahogany leaves consisting of large mahogany and small mahogany. The results of phytochemical screening on samples of lansium, duku, chinaberry, large mahogany and small mahogany in the n-hexane, ethyl acetate and water fractions showed positive results for flavonoids and steroids, while for alkaloids, terpenoids and saponins showed negative results. The results of the analysis showed that small mahogany plants contained high starch content of 43.72 g/mL, high fat content of small mahogany plants of 24.15% and high protein content of Langsat plants of 9.01 g/mL. The level of preference Hypsipyla sp prefers small mahogany plants compared to other plants. The number of mahogany stomata compared to other plants regulates the rate of evaporation in which will also release secondary metabolic compounds as attractants to attract insects to plants. The main flavonoid groups in mahogany are Quercetin 3-O-β-D-galactopyranoside, Quercetin 3-O-β-D-glucopyranoside, and quercetin 3-O-α-L-rhamnopyranoside.  Key words: phytochemicals; plant metabolites; quercetin; mahogany; Hypsipyla sp.